Peter's legacy in early Christianity: the appropriation and use of Peter's authority in the first three centuries - Eurell, John-Christian (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2021)
John-Christian Eurell studies how Peter's authority is portrayed to create legitimacy in Christian texts. Peter emerges as a central figure in the diverse early Christian movement and is used to discuss theological legitimacy. The main divide is between those who argue that legitimate theology should have a conservative point of departure based on traditional material handed down from the earthly Jesus and an apostolic succession based on interpersonal relations and those who argue in favour of a more progressive point of departure which places emphasis on contemporary charismatic experiences. These perspectives are utilised by groups of various theological persuasions to argue their own position. Peter is seen as a positive and negative example for both these ways of creating legitimacy